Cyclic voltammetry, electrochemical impedance and ex situ X-ray diffraction studies of electrochemical insertion and deinsertion of lithium ion into nanostructured organic-inorganic poly(3,4-ethylenedioxythiophene) based hybrids - Vadivel Murugan, A. (2014)
10.1016/j.jelechem.2007.02.013